Effects of microbial inoculation on enzyme activity, available nitrogen content, and bacterial succession during pig manure composting. (June 2020) - Li, Changning; Li, Haiyun; Yao, Tuo; Su, Ming; Li, Jianhong; Liu, Ziyue; Xin, Yuqiong; Wang, Lide; Chen, Jiangang; Gun, Shuangbao
Highlights: Microbial inoculation advanced composting into the thermophilic stage by 2 days. It increased phosphatase, sucrose, and catalase activities at the maturity stage. Microbial inoculation reduced human disease-related functional gene levels. It increased Moraxellaceae, Planococcaceae, and Thermonosporea abundance at the family level. NO3 − -N remained stable and unchanged during the cooling and maturity stages. Abstract: This study evaluated enzyme activity, available nitrogen, and bacterial succession during pig manure composting with and without microbial inoculation (ABB and CK, respectively). ABB reached the thermophilic stage 2 days than CK. Cellulose, urease, phosphatase, and sucrase activities were higher in ABB than in CK on days 12–24 of composting, but catalase activity was lesser in ABB than in CK throughout composting. NH4 + -N and NO3 − -N were significantly increased in ABB at the maturity stage. 16S rRNA sequencing revealed Nocardiopsaceae, Bacillaceae, Streptosporangiaceaec, Flavobacteriaceae, and Caldicoprobacteraceae as the dominant bacteria at the family level. Metabolism function analysis revealed that human diseases were reduced and carbohydrate metabolism was increased in ABB. Correlation analysis revealed that urease, sucrose, and phosphatase were significantly correlated with bacteria at the species level, whereas NH4 + -N and NO3 − -N were not significantly correlated. These results indicated that microbial inoculation accelerated the composting process and significantly regulated microbial functions.